2018
DOI: 10.29252/jfqhc.5.3.89
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of Cryptosporidium spp. Oocysts in Raw Vegetables Produced in Koya City, Iraq

Abstract: HIGHLIGHTS  The average prevalence rate of Cryptosporidium was 6.5% in vegetables of Koya, Iraq.  Contamination rates were not related to vegetable types and also sampling seasons.  Serious control measures and training must be carried out in the studied area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The quality of irrigation water was usually incriminated in the presence of waterborne parasites in fresh produce. Indeed, several studies found that the use of raw water in irrigation leads to contamination of vegetables with G. duodenalis (Amahmid et al ., 1999; Daryani et al ., 2008; Abougrain et al ., 2010; Amoros et al ., 2010; Shahnazi and Jafari-Sabet, 2010), and Cryptosporidium (Sleman Ali et al ., 2018) or both parasites (Amoros et al ., 2010). Another factor contributing to the contamination of crops with Cryptosporidium is the fertilization using manure from cattle and sheep, containing viable oocysts of Cryptosporidium (Moore et al ., 2007; Rzezutka et al ., 2010; Sleman Ali et al ., 2018), because oocysts can remain viable in manure for several months (Bukhari, 1995), and in soil for several weeks especially at low temperature (Nasser et al ., 2007).…”
Section: Literature Selection Criteriamentioning
confidence: 99%
“…The quality of irrigation water was usually incriminated in the presence of waterborne parasites in fresh produce. Indeed, several studies found that the use of raw water in irrigation leads to contamination of vegetables with G. duodenalis (Amahmid et al ., 1999; Daryani et al ., 2008; Abougrain et al ., 2010; Amoros et al ., 2010; Shahnazi and Jafari-Sabet, 2010), and Cryptosporidium (Sleman Ali et al ., 2018) or both parasites (Amoros et al ., 2010). Another factor contributing to the contamination of crops with Cryptosporidium is the fertilization using manure from cattle and sheep, containing viable oocysts of Cryptosporidium (Moore et al ., 2007; Rzezutka et al ., 2010; Sleman Ali et al ., 2018), because oocysts can remain viable in manure for several months (Bukhari, 1995), and in soil for several weeks especially at low temperature (Nasser et al ., 2007).…”
Section: Literature Selection Criteriamentioning
confidence: 99%
“…For instance, in Iraq, the average prevalence rate of Cryptosporidium in vegetables was 6.5%. Likewise, a study conducted in Korea detected Cryptosporidium spp.in various raw vegetables, including lettuce, perilla leaves, and watercress [105,106]. The main source of contamination for these vegetables is often the use of contaminated irrigation water during their cultivation in fields.…”
Section: Cryptosporidium Sppmentioning
confidence: 99%